The performance of isolated half-scissor like elements mechanism under compression axial load - Chai, Teck Jung; Tan, Cher Siang; Koh, Heng Boon (Penerbit Universiti Kebangsaan Malaysia, 2023)
Half-Scissor Like Elements (H-SLEs) deployable mechanism is the prefab scissor based structural mechanism consists of two bars with bolted connection to enable structure change shape. An experimental investigation on the isolated H-SLEs deployable mechanism under compression axial load was presented. A total of twelve specimens were fabricated in two series with six specimens each series were tested on their strength and stability at deployed configuration. The test specimens in series 1 mm thick C75 section were namely S1, S2, S3, S4, S5 and S6 while series 0.75 mm thick C 75 section were namely S7, S8, S9, S10, S11 and S12. The test specimens consist of C 75 and C 100 section which connected with M6, M8 and M10 bolt in grade 8.8. The compression axial load was applied at the center of 3 mm thick loading platform. The experimental results obtained indicated that four types of failure modes observed, i.e. bolt bending failure, section bearing failure, member buckling failure and instability due to horizontal displacement at mid-height of H-SLEs deployable mechanism (Bolted joint area). Among these failure modes, bolt bending failure was dominated the overall structure stability and impacts others failure modes indirectly while section thickness has impacted the buckling and bearing failure. The ultimate load capacity over BS EN 1993 design bearing resistance ratio obtained for M10 bolt was satisfactory. Besides, twisted effect observed during load applied also contributed to the failure modes identified. Thus, the H-SLEs deployable mechanism with stiffener with M10 bolt connection is necessary for future research in the application of spatial deployable structure purposes.